Fate calculation experts : diviners seeking legitimation in contemporary China - Li, Geng, 1985- (Asian anthropologies, 2019)
Having long been stigmatized as an immoral and even illegal 'superstition', the popular practice of divination is experiencing a revival in contemporary China. Fate Calculation Experts explores how diviners attempt to achieve legitimation in a society which identifies strongly with modernity, science, and rationality. As well as associating with modern knowledge production systems, diviners build a positive social image for their occupation via claims to moral authority and appeals to 'tradition'. Beyond matters of image management, diviners' efforts towards legitimation also figure in the social relationships and fundamental cultural values they develop in their practice.